NEXAFS and XPS of p-Aminobenzoic Acid Polymorphs: The Influence of Local Environment. (May 2016) - Stevens, J S; Gainar, A; Jaye, C; Fischer, D A; Schroeder, S L M
Abstract: Nitrogen K-edge XPS and NEXAFS of the two polymorphic forms of para - aminobenzoic acid (PABA) are significantly different reflecting variation in hydrogen bonding. Alteration in hydrogen bonding at the amino group leads to a shift to high energy for both the XPS N 1s core level and the 3π* NEXAFS resonance with β-PABA. Participation of the amine group in the aromatic system causes the 1π* resonance to be sensitive to the nature of the intermolecular bonding at the para-carboxylic acid group, and a shift to low energy for α- PABA is observed due to hydrogen-bonded carboxylic acid dimer formation. FEFF calculations also successfully reproduce both the energy and intensity variations observed for the σ* shape resonance associated with the C-N bond, with the majority of the decrease in energy observed for b-PABA arising from the longer C-N bond.